DONOR CHIMERISM IN PATIENTS WITH PRIMARY IMMUNODEFICIENCY AFTER ALLOGENEIC HEMATOPOIETIC STEM CELLS TRANSPLANTATION - V. A. Lavrinenko; Y. E. Marejco; E. Y. Berezovskaya; M. V. Stegantseva; N. V. Minakowskaja; M. V. Belevtsev (Онкогематология)
Allogeneic stem cell transplantation (alloHSCT) is effective curative option for a broad range of primary immunodeficiencies (PIDs). Hematopoietic chimerism monitoring in patients with various PIDs and its connection with the outcome of alloHSCT is of great interest. In this study 16 alloHSCT in patients with PIDs were included. Three-year overall survival was 72.2 ± 12.0 %. Full donor chimerism (FDC) was achieved in 13 (81.25 %) patients. Prolonged persistence of mixed chimerism (MC) was observed in 3 (18.75 %) patients. In patients with MC in the peripheral blood, circulating T-cells are completely or predominantly of donor origin, whereas granulocytes are predominantly or completely recipient cells, and chimerism in B-cells differs significantly from 0 % chimerism to FDC. In patients with PIDs, engraftment of individual cell lines (split chimerism) could be observed. In some patients chimerism decreased during the first year after alloHSCT with its subsequent stabilization. Increasing MC is not associated with transplant rejection in PIDs. FDC in patients with PIDs provides restoration of all cell lines participating in the immune response regardless of the diagnosis, but it is associated with more frequent development of «graft-versus-host» disease (GVHD), which is a serious complication of alloHSCT and can lead to treatment-related mortality (TRM). MC/split chimerism, in which the frequency of development of GVHD is less, can also provide the formation of a full immune response and correction of other disease manifestations, but only when replacing defective cell lines according to the diagnosis.